Proceedings of the International Conference on Logistics, Engineering, Management and Computer Science 2014
DOI: 10.2991/lemcs-14.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

A review of algorithms for order batching problem in distribution center

Abstract: Abstract-Order batching is pivotal for the efficiency of order picking operations so that researches on this problem are prevalent. The aim of this paper is to analyze and summarize the range and idea of order batching by giving an review of the different solution approaches which have been suggested in the literature, and at last indicate tendency of future research of order batching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…In addition to same-day delivery with simplified routing costs, one-dimensional models have application in other areas where a vehicle or machine's movement is constrained along a single dimension; see [22,23,57]. Also, our model is closely related to the Order Batching Problem (OBP) [25,42], which determines optimal assignment of pick orders to batches and the pick tour sequence for each batch in warehouse operations. The Dynamic Order Batching Problem (DOBP) is an extension with orders arriving dynamically while the decision maker processes previous orders; see [13].…”
Section: Vehicle Routing and Dispatch Problemsmentioning
confidence: 99%
“…In addition to same-day delivery with simplified routing costs, one-dimensional models have application in other areas where a vehicle or machine's movement is constrained along a single dimension; see [22,23,57]. Also, our model is closely related to the Order Batching Problem (OBP) [25,42], which determines optimal assignment of pick orders to batches and the pick tour sequence for each batch in warehouse operations. The Dynamic Order Batching Problem (DOBP) is an extension with orders arriving dynamically while the decision maker processes previous orders; see [13].…”
Section: Vehicle Routing and Dispatch Problemsmentioning
confidence: 99%
“…Bu nedenle çözüm algoritmaları daha çok sezgisel veya meta-sezgisel yöntemlerden oluşmaktadır. Ma ve Zhao (2014) literatürde bulunan ve sipariş yığınlama problemi için kullanılmış sezgisel ve meta-sezgisel algoritmalarla ilgili yayınları incelemişler ve sınıflandırmışlardır. Sipariş toplama modelleri çoğunlukla paralel raf sistemi ve tek toplayıcılar için çözümlenmiştir.…”
Section: Li̇teratürunclassified
“…Making order picking less laborious is also important to improving efficiency (Ho et al, 2008;Thomas and Meller, 2015). A number of articles have reported that it accounts for as much as 55% (De Koster et al, 2007;Tompkins et al, 2010), 50-65% (Ma and Zhao, 2014), 60-65% (Henn, 2012), or even 60-70% (Chen et al, 2015) of warehousing costs.…”
Section: Introductionmentioning
confidence: 99%